EVALUATION OF MICROBIAL RESISTANCE AGAINST CEFTRIAXONE IN PATIENTS REFERRED TO HEALTH CENTERS IN KABUL, 2021-2022 - Murtaza Jafari; Abdulbasit Taib; Tahmina Shamriz (Journal Park Publishing, 2022)
Introduction: Antibiotics are a major group of medicine that is considered a special aspect of medicine today. This group of medicine has the ability to kill microorganisms or prevents them from growing, but today, due to their unreasonable use, their effectiveness and susceptibility to microorganisms have decreased.Objectives of the Study: The main purpose of this study was to evaluate and determine the level of microbial resistance to the antibiotic Ceftriaxone in patients referred to health centers in Kabul. Ceftriaxone is a broad-spectrum antibiotic that is used in a variety of infections, but due to its unreasonable use, microbial resistance to this antibiotic has developed.Research Method: This research is a retrospective cross-sectional study in which pathological samples and their anti-biogram results were collected from some diagnostic laboratories related to health centers in Kabul during the second 6 months of (2021-2022).Results: In this study, (354) anti-biogram test results were collected from diagnostic laboratories in Kabul, so that the highest microbial resistance to Oxacillin (92%) and the lowest microbial resistance to Levofloxacin and piperacillin (0%) were reported. Microbial resistance to ceftriaxone (52.38%) was also reported in this study.Conclusion: Microbial resistance is a dangerous and threatening phenomenon of human health, which is directly related to the unreasonable prescription of antibiotics. Unfortunately, due to the arbitrary and unreasonable use of ceftriaxone, microbial resistance to this broad-spectrum antibiotic has developed.
Keywords: Microbial resistance; Antibiotics and Ceftriaxone